Designing an Open Innovation Model Based on Sustainable Ethical Behaviors Using Textual Content Analysis Approach - Hosseini, Seyyedeh Elham; Kia Kojouri, Davood; Rahmaty , Maryam; Hajiaghajani , Azam (Management Strategies and Engineering Sciences, 2024)
Given the unrestricted nature of knowledge in today's world and the dissolution of rigid boundaries between organizations and even countries, the concept of closed innovation has been replaced by open innovation. Organizations are transitioning from closed innovation to open innovation, which represents one of the most complex stages of the innovation process. Sustainable business ethics is considered a crucial issue for organizations, and the lack of recognition of its related indicators can lead to negative consequences in society. The present study aims to design an open innovation model based on sustainable ethical behaviors using a textual content analysis approach. Accordingly, 45 domestic articles and 77 international articles were utilized. Based on the content analysis approach, the identified factors include individual factors with six criteria (respectful behavior, honesty, conscientiousness, benevolence, prudent behavior, and knowledge sharing), organizational factors with six criteria (meritocracy, support, workplace spirituality, informed decision-making, fair evaluation, and excellence), and environmental factors with five criteria (law compliance, technology, scholarly interaction, supportiveness, and trust). These factors collectively contribute to open innovation based on sustainable ethical behaviors.